Czynności sprawdzające a postępowanie podatkowe - Grzybowski, Paweł (Kwartalnik Prawa Podatkowego, 2015)
This article is an analysis of the current Tax Ordinance. The main theme of this paper is the essence of the measures of control and answer to the question of the importance of this institution for tax liability. The article shows the dependences between the measures of control and the tax proceeding. The analysis allows to identify those areas in terms of normative the measures of control, which in practice can duplicate the assumptions of jurisdictional tax proceeding. Current work on creating a „new Tax Ordinance”, require analysis of the current regulations in order to identify areas in need of normative explanation. Therefore, in the conclusion the author indicates a collection of postulates for the legislature. The whole discussion revolves around the verification of the thesis, according to which the measures of control are separate from the tax proceedings. The author postulates a continuation of the isolation the measures of control in the „new Tax Ordinance”, but points that it is need of eliminate errors of the applicable regulations.